A Metacognition-Based Digital Microlearning Platform: The Usability Evaluation - Yudantoko, Afri; Wahyudi, Kurniawan Sigit; Fatin, Nabila Naila; Rahmadonna, Sisca; Fathoni, Muhammad Ihsaan (Faculty of Engineering, Universitas Negeri Yogyakarta, 2025)
This study examined the usability of a metacognition-based microlearning platform developed through a design-based research (DBR) framework. The evaluation was carried out in the sixth stage of the DBR cycle, evaluation and reflection, to validate its practicality and effectiveness as an instructional tool. A quantitative approach was applied using the Usefulness, Satisfaction, and Ease of Use (USE) Ques-tionnaire, administered to 252 students enrolled in the Automotive Vocational Teacher Education pro-gram in 4 different universities. The questionnaire consisted of 30 items on a 7-point Likert scale, as-sessing four dimensions: usefulness, ease of use, ease of learning, and satisfaction. Data were analyzed descriptively by calculating means, standard deviations, and categorical levels. The results indicated very high usability across all dimensions, with mean total scores of 53.33 for usefulness, 73.46 for ease of use, 26.63 for ease of learning, and 46.62 for satisfaction. These findings demonstrate that the learn-ing platform is highly usable, functionally effective, and well received by students.